Information Technology and Open Source: Applications for Education, Innovation, and Sustainability c - Cerone, Antonio; Persico, Donatella; Fernandes, Sara.; Garcia-Perez, Alexeis; Katsaros, Panagiotis; Shaikh, Siraj Ahmed; Stamelos, Ioannis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes revised selected papers from the following SEFM 2012 satellite events: InSuEdu, the First International Symposium on Innovation and Sustainability in Education; MokMaSD, the First International Symposium on Modelling and Knowledge Management for Sustainable Development and Open Cert, the 6th International Workshop on Foundations and Techniques for Open Source Software Certification, held in Thessaloniki, Greece, in October 2012. The total of 14 regular papers and 7 short papers included in this volume were carefully reviewed and selected from 35 submissions. The papers cover the topics related to the use of Information and Communication Technology (ICT) and Open Source Software (OSS) as tools to foster and support Education, Innovation and Sustainability.
Innovation and Sustainability in Education -- Inquiry-based science education in secondary school informatics challenges and rewards -- Innovation and sustainability in higher education: lessons learnt from the case study of an online university -- Mobile augmented reality with audio; supporting fieldwork of Cultural sciences students in Florence -- Mathematical literacy as a condition for sustainable development -- Learning CSCW by Fairytales: a Practical Model -- The Role of Peer Review in Supporting the Sustainability of Technology-Enhanced Learning Environments -- Creative Classrooms: A Systemic Approach for Mainstreaming ICT-enabled Innovation for Learning in Europe -- FLOSS in Technology-Enhanced Learning -- A preliminary analysis of learning awareness in FLOSS projects -- Concept and Experiences on using a Wiki-based System for Software-related Seminar Papers -- Modelling and Knowledge Management for Sustainable Development -- Algorithmic Systems Ecology: Experiments on Multiple Interaction Types and Patches -- Modelling Population Dynamics Using Grid Systems -- Transition to sustainability: Italian scenarios towards a low-carbon economy -- Models of Knowledge Transfer for Sustainable Development -- A Framework for Translating Legal Knowledge into Administrative Processes: Dynamic Adaption of Business Processes -- Model-Based Tool Qualification: The Roadmap of Eclipse towards Tool Qualification -- Secure Migration of Legacy Applications to the Web -- A Web Portal for the Certification of Open Source Software -- Open Source Software Process: A Potential Catalyst for Major Changes in Electronic Health Record Systems -- Using Open Source Projects in Higher Education: A Two-Way Certification Framework -- Guidelines for the application of Data Envelopment Analysis to assess evolving software -- A Certification Process for Android Applications.
Keywords: Computer science; Software engineering; Artificial intelligence; Computer simulation; Education -- Data processing; Computers and civilization; Computer Science; Computers and Education; Software Engineering; Simulation and Modeling; Computers and Society; Artificial Intelligence (incl. Robotics).; Electronic books